013 Paramedic HEART scores in the prediction of MACE and AMI. The ambulance cardiac chest pain evaluation in scotland (ACCESS) study. Issue 12 (21st November 2019) - Cooper, Jamie; Ferguson, James; Donaldson, Lorna; Black, Kim; Davidson, Elaine; Horrill, Judith; Livock, Kate; Lee, Kuan Ken; Anand, Atul; Mills, Nicholas; Scott, Neil
Abstract : Background: Cardiac sounding chest pain represents about 5% of all Emergency Department (ED) attendances in the United Kingdom (UK), often via 999 ambulance. Much work has focused on the rapid distinction of the 1 in 5 patients without ST elevation on ECG, who are suffering from a non ST elevation myocardial infarction (NSTEMI). Pre-hospital translation of such work may allow improved access to specialist treatment for patients with NSTEMI and also identify a low risk population suitable for management without immediate ambulance transfer to hospital. The objective was to determine the accuracy of a wholly paramedic calculated pre-hospital HEART score to predict a 30-day Major Adverse Cardiac Event (MACE). The potential implications of pre-specified low-risk and high-risk cut offs were also to be determined. Method and results: Prospective diagnostic accuracy study in Northeast Scotland (UK) on adult (>18 yr) patients with cardiac sounding chest pain, attended by a paramedic ambulance and who had no ST elevation on initial ECG. A real time paramedic HEAR score was calculated and blood drawn for analysis with a POC cTn assay and later with both laboratory based contemporary and high-sensitivity cTn assays. Normal care then ensued and patients were followed up to 30 days for development of MACE. Conclusions: Between Nov 2014 and April 2018, 1275 patients agreed to participate in the ambulance and 1056 later gave informed consent with 1054 completing 30 day follow up. 358 patients had complete Paramedic HEART scores with all 3 assays and 969 patients with the 2 lab based assays (figure 1 ) Sensitivities and specificities (95% CI) for the HEART scores vs MACE will be calculated and ROC curves generated. Diagnostic properties at different score cut-offs will be presented and analysis of the impact of the different cTnI assays presented. Apologies: Independent AMI adjudication due to complete next week, so no full results yet.